Quality of life among lymphoma survivors in a developing country - Diana Ng, Leh Ching; Gan, G. G.; Leong, Y. C. (Elsevier Inc., 2015)
Aim/Background: To evaluate the health-related quality of life (HRQoL) of lymphoma survivors in Malaysia and to determine the clinical and psychosocial factors which may affect their quality of life (QOL). Methods: This cross sectional study was conducted in hematology clinic at University Malaya Medical Centre. HRQoL was assessed using validated European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30). Depression and anxiety symptoms were assessed using validated Hospital Anxiety and Depression Scale (HADS). Multiple linear regression analysis was used to determine association of sociodemograhic and clinical characteristics with each QOL items. Results: In total, 156 patients participated (93% response rate). The mean score of global health status/ quality of life measured 76.17. Fatigue was the most frequent reported symptom (53.2%) followed by insomnia (50.0%) and financial difficulties (48.7%). Females had poorer emotional functioning and greater fatigue compared to males, mean score 33.45 vs 25.74 (p = 0.039). Lower education level was associated with poorer physical functioning (p = 0.018). Higher anxiety score was associated with poorer scores in all functional scales and worse symptoms such as insomnia and financial difficulties (p < 0.05). Having additional comorbidities was associated with poorer physical and cognitive functioning, greater fatigue and insomnia (p < 0.005). Hodgkin’s lymphoma was associated with poorer emotional functioning (p = 0.010). Conclusions: The mean global health score of 76.1 is comparable to other studies done in developed countries. The main symptoms of the lymphoma survivor found in this study was fatigue. Presence of anxiety symptoms affect the functions of these patients and routine monitoring maybe required in order to improve QOL. It is also noted that patients with history of Hodgkin lymphoma appeared to have a poorer emotional functioning and this probably warrant further exploration. Health care providers need to be more sensitive to the aspect of fatigue and emotion symptoms particularly anxiety and to provide further support to these patients to further improve their QOL.